Formation of Super-Earths and Mini-Neptunes from Rings of Planetesimals - Sho Shibata; Andre Izidoro (The Astrophysical Journal Letters)
The solar system's planetary architecture has been proposed to be consistent with the terrestrial and giant planets forming from material rings at ∼1 au and ∼5 au, respectively. Here, we show that super-Earths and mini-Neptunes may share a similar formation pathway. In our simulations conducted with a disk α -viscosity of 4 × 10 ^−3 , super-Earths accrete from rings of rocky material in the inner disk, growing predominantly via planetesimal accretion. Mini-Neptunes primarily originate from rings located beyond the water snowline, forming via pebble accretion. Our simulations broadly match the period-ratio distribution, the intrasystem size uniformity, and the planet multiplicity distribution of exoplanets. The radius valley constrains the typical total mass available for rocky planet formation to be less than 3–6 M _⊕ . Our results predict that planets at ∼1 au in systems with close-in super-Earths and mini-Neptunes are predominantly water-rich. Though relatively uncommon, at ∼1% level, such systems might also host rocky Earth-sized planets in the habitable zone that underwent late giant impacts, akin to the Moon-forming event.